Rental Building and Event Equipment Application at the Arcadia Function Hall Web-Based - Mulyati, Mulyati; Supriadi, Ajay; Imaduddin, Alim (Pandawan, 2019)
The Journal Website is one of the tools used as a means of information and communication that is able to get rid of all the limitations that exist in other information and communication tools. One of the limitations of communication and information tools is about distance, with websites we can find various information in various parts of the world. At Arcadia Function Hall the building leasing process is done manually, so that the time spent is ineffective and in the storage of rental data it becomes insecure because it is not stored in a good system. From the above problems the authors are interested in designing Web Based Applications to be able to help the building rental process performance become more effective and efficient and can store all rental data safely and can produce accurate and accurate reports.